Two-dimensional layered architecture constructing energy and phonon blocks for enhancing thermoelectric performance of InSb - Xin, Jiwu (2022)
InSb is a narrow-bandgap semiconductor with a zinc blende structure and has been wildly applied in photodetectors, infrared thermal imaging, and Hall devices. The facts of decent band structure, ultrahigh electron mobility, and nontoxic nature indicate that InSb may be a potential mid-temperature thermoelectric material. The critical challenges of InSb, such as high thermal conductivity and small Seebeck coefficient, have induced its ultrahigh lattice thermal conductivity, and thus low ZT values. In view of this, we have developed a competitive strategy typified by the cost-efficient nanocompositing of z wt% QSe2 (Q = Sn, W). Specifically, the QIn+ and SeSb+ point defects were introduced in the InSb system by nanocompositing the vested two-dimensional layered QSe2. In addition, the enlarged valence band maximum of intrinsic WSe2 acted as ladders can scatter a fair number of hole carriers, resulting in the relatively enhanced Seebeck coefficient of high temperature. Moreover, the disorderly distributed nanosheets/particles, and dislocations acting as obstacles can effectively delay the heat flow diffusion, inducing the strong scattering of thermal phonons. Consequently, an enhanced power factor of ∼33.3 µW cm−1 K−2 and ZT value of ∼0.82 at 733 K have been achieved in the 3% WSe2 sample, companied with the engineering output power density ωmax ∼233 µW cm−2 and thermoelectric conversion efficiency η ∼5.2%. This artificially designed approach indicated by suited nanocompositing can integrate several engineering strategies such as point defects, nanoengineering, and energy filtering into one, providing a reference to optimize the thermoelectric performance of other thermoelectric systems. [Figure not available: see fulltext.]